Dependence of egg hatching on Wolbachia density in a parthenogenetic weevil revealed by antibiotic treatment - Rodriguero, Marcela Silvina; Scannapieco, Alejandra Carla; Monti, Daniela S.; Chifflet, Lucila; Elias-Costa, Agustín J.; Lanteri, Analía A.; Confalonieri, Viviana A. (Wiley, 2021)
Naupactini is a tribe of Neotropical broad‐nosed weevils highly diverse in South America. This group includes several parthenogenetic species, some of them harmful for agriculture and invasive around the world. Although some hypotheses based on polyploidy and hybridization have been proposed to explain the origin of parthenogenesis in weevils, the infection with the bacterium Wolbachia pipientis may be involved in the origin of parthenogenetic reproduction of some species. In this contribution, we studied the role of Wolbachia in the reproductive biology of Pantomorus postfasciatus Hustache (Coleoptera: Curculionidae) through a curing experiment using tetracycline. This weevil has a mixed mode of reproduction including sexual and parthenogenetic populations. Exposure to an antibiotic did not affect fecundity, but did reduce egg hatching in comparison with untreated individuals. Consequently, we inferred that Wolbachia most probably takes part in the reproduction of P. postfasciatus, either by exerting nutritive functions in oogenesis necessary for egg hatching, or by induction of thelytokous parthenogenesis. Although infection was not totally cured, Wolbachia load was significantly lower in treated than in control females. Thereby, we hypothesize that a minimum threshold density of Wolbachia is required for weevil reproduction. We conclude that all analyses support a role of Wolbachia in P. postfasciatus reproduction.